“The Heart in the Arms of Creativity” (The Harmony of Pain, Love, and Thought in the Works of Kholyor Safarov) (Eurasian Scientific Herald, 2025)
In this article, the stories and short stories of the talented writer Kholyor Safarov are analyzed, the vividness of the writer's works, the individuality of his characters, the depiction of the complex psyche and experiences of a person, the uniqueness of the construction of the subject, the unexpected solution and the method of keeping secrets. , deep drama and symbolism, enlightenment, wisdom and national spirit, priority of national color, artistic skill of the creator, stylistic originality are researched.